CRISPR and Gene Editing in Drug Development: A Revolution in Precision Medicine - Gupta, Khushboo; Thomas, Ashley Christeena; Santwani, Vandana; Sarangi, Binit Kumar; Chandrakar, Ankush; Tiwari, Sandip Prasad (Journal of Neonatal Surgery, 2025)
The discovery and implementation of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) technology have transformed the landscape of biotechnology and precision medicine. As a revolutionary gene-editing tool, CRISPR enables targeted, efficient, and cost-effective modification of DNA, offering promising therapeutic interventions for a wide range of genetic and acquired diseases. This article provides an in-depth overview of CRISPR’s origins, mechanisms, and applications in drug development, from treating genetic disorders and enhancing cancer immunotherapies to accelerating drug discovery and developing tools against infectious diseases. It also addresses ethical considerations, regulatory frameworks, and future innovations such as base and prime editing. By exploring current trends and interdisciplinary applications, this article underscores the pivotal role CRISPR plays in shaping the future of medicine, agriculture, and synthetic biology